2014
DOI: 10.1002/ocea.5061
|View full text |Cite
|
Sign up to set email alerts
|

BomBombedKwin’: How Two Card Games ModelKula,Moka, andGoroka

Abstract: In 2009-2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Transfers are possible not because the things that move are immutable objects but because the properties of things in the social world are given immutability that appears objective (Verran 2001). Indeed, the establishment, perpetuation, or erasure of the transferred object's status as a unit may well be an important feature in identifying its politics and the social reality generating it (Pickles 2013;M. Strathern 1992).…”
Section: Transfersmentioning
confidence: 99%
See 4 more Smart Citations
“…Transfers are possible not because the things that move are immutable objects but because the properties of things in the social world are given immutability that appears objective (Verran 2001). Indeed, the establishment, perpetuation, or erasure of the transferred object's status as a unit may well be an important feature in identifying its politics and the social reality generating it (Pickles 2013;M. Strathern 1992).…”
Section: Transfersmentioning
confidence: 99%
“…Anthropologists of Melanesia share with their interlocutors an overriding concern with setting the boundaries of transactions, implicating people in transactions with appeals to definitive obligations but in the knowledge that their appeals were transparently contingent (Pickles 2013(Pickles , 2017. Like Melanesianists David Akin and Joel Robbins (1999), I found that my interlocutors "regularly work to differentiate kinds of exchanges, kinds of relationships, and kinds of objects" (9) and are anxious about the collapse of these distinctions (see also M. Strathern 1992).…”
Section: Pure Gifts Maussian Gifts Unaccompanied Transfersmentioning
confidence: 99%
See 3 more Smart Citations